Could JC virus provoke metastasis in colon cancer? - Sinagra, Emanuele (World journal of gastroenterology : WJG, 2014)
AIM: To evaluate the prevalence of John Cunningham virus(JC virus) in a small cohort of patients with colon cancer and to assess its presence in hepatic metastasis.METHODS: Nineteen consecutive patients with histologically diagnosed colon cancer were included in our study, together with ten subjects affected by histologically and serologically diagnosed hepatitis C virus infection. In the patients included in the colon cancer group, JC virus was searched for in the surgical specimen; in the control group, JC virus was searched for in the hepatic biopsy. The difference in the prevalence of JC virus in the hepatic biopsy between the two groups was assessed through the χ2 test.RESULTS: Four out of 19 patients with colon cancer had a positive polymerase chain reaction(PCR) test for JC virus, and four had liver metastasis. Among the patients with liver metastasis, three out of four had a positive PCR test for JC virus in the surgical specimen and in the liver biopsy; the only patient with liver metastasis with a negative test for JC virus also presented a negative test for JC virus in the surgical specimen. In the control group of patients with hepatitis C infection, none of the ten patients presented JC virus infection in the hepatic biopsy. The difference between the two groups regarding JC virus infection was statistically significant(χ2 = 9.55, P = 0.002).CONCLUSION: JC virus may play a broader role than previously thought, and may be mechanistically involved in the late stages of these tumors.